In vitro cytotoxic activity of ethanolic extracts of Thevetia peruviana cells cultured in bioreactor - JIMÉNEZ, Stephanie; RÍOS, Rosaly; MENDOZA, Dary; ARIAS, Juan Pablo; ARIAS, Mario (Revista Productos Naturales, 2022)
Thevetia peruviana is an ornamental plant characterized by its high content of cardiotonic glycosides with ionotropic, anti-tumoral and cytotoxic activities.
Keywords: Thevetia peruviana; cell cultures; cardiotonics; cytotoxic activity; cell viability